Uji Toksisitas Dan Uji Fitokimia Ekstrak Daun Kedondong (Spondias dulcis Parkinson) - Nur Hasanah; Arika Handayani (STIKes Kharisma Persada, 2019)
Kedondong Leaf (Spondias dulcis Parkinson) is one of medicinal plants that is grow in Indonesia. This study aims to identify the toxicity of the extract Kedondong leaf (Spondias dulcis Parkinson) and identify the class of compounds contained in the leaf extract Kedondong (Spondias dulcis Parkinson). The method used in this research is BSLT (Brine Shrimp Lethality Test) of ethanol solvent then continued with the solvent fraction of n-hexane and ethyl acetate which is used was 50 ppm, 100 ppm, 200 ppm, 400 ppm, 600 ppm and 1000 ppm which each concentration was made into 2 then added 10 larvae each (Artemia salina Leach). Observation of dead larvae was performed 24 hours after administration of the extract. Mortality data using probit analysis showed that ethanol extract had LC50 value of 56,4806 ppm, ethyl acetate extract had LC50 value of 66,9730 ppm and n-hexane extract had LC50 value of 447,7133 ppm. The results showed that the three phases of extract Kedondong leaf (Spondias dulcis Parkinson) were used are having potential toxic effect on larvae (Artemia salina Leach) because they have LC50 <1000 ppm and group of compounds extract Kedondong leaf (Spondias dulcis Parkinson) contains alkaloid, compounds, saponins, tannins, phenolic, flavonoids, triterpenoids, steroids, and glycans.